THE ANALYSIS OF INVESTMENT, INFLATION, DISTRICT’S MINIMUM WAGE AND EDUCATION ON LABOR ABSORPTION IN SIDOARJO 2002-2017 - Mediasari Soraya Sukoto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The main problem in employment, especially in Sidoarjo is located in the level ofemployment opportunities. Some theoretical determinant of the factors that canaffect employment is Investment, Inflation, Distric's Minimum Wage, andEducation that need to be examined in Sidoarjo City. The research aims todetermine how much the influence on Investment, Inflation, District’s MinimumWage, and Education on labor absorption in Sidoarjo City. The analytical methodin this research is panel data regression with 18 sub-districts in Sidoarjo Cityduring 2002-2017. The best model that can be used in this study is a randomeffect model. The research showed that Investment and Inflation are positive butnot significantly influence on labor absorption in Sidoarjo. But Wage andEducation is positive significantly influence on labor absorption in Sidoarjo.Keywords : Investment, Inflation, Distric’s Minimum Wage, Education, LaborAbsoprtion